Talent Retention in Telecommunication SMEs: Emerging Challenges and Prospective Solutions - Momin, Mujtaba M. (International Journal of Advanced Science and Technology, 2020)
The current study tries to understand the phenomenon of talent turnoverby means of Employee Voluntary Attrition. For emerging Telecommunication SMEs (small-to-medium enterprise), besides the tangible technological resources, the intangible intellect or human capital is of extreme importance. A persistent drain of these intellectual forces, make it tough for the organizations to survive & hence the current study is intended to understand the conjugal relation between the event of Employee Voluntary Attrition & various dependent variables that tune-in. The papers shall empirically study the event of Employee Voluntary Attrition (EVA) in a specific geography as elaborated in the study. The workshop shall try to focus on the Attrition (EVA) in congruence with the dependent variables of Monetary Dissatisfaction, Leadership, Job Specification – Environment, Work Hours – geography & its tune with the Dependent Variable. The study indicates that the significance of Leadership & Money is one of the most influential factors of Employee Attrition. The current study also proposes to check the influence of Employee Attrition on the growth of Telecom SMEs& its significant effect on the Financial Health of the Organizations. The study finds no significance between the event of Employee Attrition & geographical proximity as a variable.